O uso de elementos sensoriais no ponto de venda aumenta os índices de atratividade, lealdade e preferência dos shoppers à loja?: uma reflexão crítica - Almeida, Keyla Priscila dos Reis de (2013)
This paper analyzes how sensory marketing applied to the point of sales affects store attractiveness and shopper loyalty and preference levels. Experiential marketing has gained importance in a context in which physical shopping channels are not only increasingly competing with each other, but also being challenged by the online channel, which offers more convenience and, in some cases, better prices. One must bear in mind that shoppers are overwhelmed with visual stimuli and tend to respond better to stimuli involving more than one sense. This dissertation is a multiple case study which aims to compare loyalty and preference rates between two Carrefour hypermarkets: one with a traditional concept and another with the Planet concept. In the light of the ever-growing difficulties in differentiating hypermarkets from other channels, Carrefour Planet is an attempt on Carrefour's part to restructure its hypermarkets through purchase solution centers, in which each department conveys a differentiated atmosphere, focused on exploiting its key items and sensory elements. Despite Carrefour's efforts to differentiate its hypermarkets we conclude from this study that the sensory management approach did not promote an increase in shopper loyalty and preference rates when we compare a Carrefour Planet and a traditional Carrefour store, although the Planet store did stand out as the most attractive. We recommend the development of future studies comparing loyalty and preference rates for the same point of sale (before and after the employment of sensory elements)